2020
DOI: 10.1002/jmv.26529
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and factors associated with serum HBV pregenomic RNA levels in Chinese chronic hepatitis B patients

Abstract: Correlations between serum hepatitus B virus (HBV) pregenomic RNA (pgRNA), hepatitus B surface antigen (HBsAg), and hepatitus B core‐related antigen (HBcrAg) levels, and influencing factors of serum HBV pgRNA levels in Chinese chronic hepatitis B (CHB) patients are rarely reported. This was a retrospective cohort study consisting of 204 outpatients with CHB. Serum levels of HBV pgRNA, HBsAg, and HBcrAg were quantitative measured in frozen blood samples. The linear regression and multivariate logistic regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 19 publications
4
13
1
Order By: Relevance
“…Additionally, a strong correlation between serum HBV DNA and serum HBV RNA levels in treated and untreated patients has been reported [ 22 , 32 , 40 , 42 ]. However, this correlation has not been consistently observed in treatment-naïve patients [ 39 , 43 ]. Serum HBV RNA was also found to correlate with HBcrAg [ 39 ] and moderately correlate with HBsAg and HBeAg quantities [ 40 ] in treatment-naïve patients.…”
Section: Novel Hbv Biomarkersmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, a strong correlation between serum HBV DNA and serum HBV RNA levels in treated and untreated patients has been reported [ 22 , 32 , 40 , 42 ]. However, this correlation has not been consistently observed in treatment-naïve patients [ 39 , 43 ]. Serum HBV RNA was also found to correlate with HBcrAg [ 39 ] and moderately correlate with HBsAg and HBeAg quantities [ 40 ] in treatment-naïve patients.…”
Section: Novel Hbv Biomarkersmentioning
confidence: 99%
“…Serum HBV RNA was also found to correlate with HBcrAg [ 39 ] and moderately correlate with HBsAg and HBeAg quantities [ 40 ] in treatment-naïve patients. Studies involving univariate analysis of treatment-naïve patients have shown that serum HBV RNA levels are significantly associated with age, HBeAg status, HBV genotype [ 40 , 43 ] as well as HBV DNA, HBsAg and HBcrAg levels [ 43 ]. The presence of pre-core or basal core promotor (BCP) mutations were also found to be positively associated with serum HBV RNA levels by multivariate linear regression [ 40 , 43 ].…”
Section: Novel Hbv Biomarkersmentioning
confidence: 99%
See 3 more Smart Citations